Rodzina w świetle Karty Praw Rodziny - Babicki, Zbigniew (Pedagogika Społeczna Nova, 2021)
The Charter of the Rights of the Family presents a succinct Christian viewpoint on a number of the most important problems of family life. By assumption, it is addressed primarily to governments repre- senting various cultures, which take responsibility for the common good, model and point of reference for building appropriate legislation and family policy, as well as setting directions for specific actions. The Charter includes provisions on ensuring families with appropriate moral, educational, social and economic conditions. The Charter explicitly emphasizes the right of parents to educate their children in accordance with their moral and religious beliefs, taking into account the cultural traditions of the family, and to decide on the education of their children. It is an important document which indicates the direction of (re) building the legal and mental system of society in the approach to the institution of the family in the light of the social teaching of the Church. The aim of the article is to try to show the topicality of the Charter of Family Rights in the life of a modern family and the functioning of the state. The text focuses on selected areas related to the fundamental rights of the family, its identity, the family as an educational environment and the need for appropriate support and help for the family.